A multi-component lithium metal alloy material and preparation method thereof

By designing multivariate lithium metal alloy materials and building a three-dimensional fast transmission network of electron-lithium ions, the problems of capacity attenuation and instability of lithium metal batteries under high current density conditions are solved, and the cycle life and electrochemical performance are significantly improved.

CN119776709APending Publication Date: 2025-04-08ZHEJIANG FUNLITHIUM NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411825824.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Under fast charging and discharge conditions, the high working current density of lithium metal batteries leads to attenuation and instability of electrode capacity, and the prior art has limited effects under this condition.

Method used

A multivariate lithium metal alloy material is designed, including 15-20% Cu, 5-10% metal element A, and 0.5-5% compound B, with the balance Li and impurity elements. An electron-lithium ion three-dimensional fast transmission network is constructed through a specific alloy preparation method.

Benefits of technology

This multi-component lithium metal alloy material can significantly inhibit the growth of lithium dendrites and the generation of dead lithium, and improve the cycle life and electrochemical performance of lithium metal batteries, especially under high current density conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005184259490000091
    Figure BDA0005184259490000091
  • Figure HDA0005184259500000011
    Figure HDA0005184259500000011
Patent Text Reader

Abstract

The invention discloses a multinary lithium metal alloy material and a preparation method thereof. The multinary lithium metal alloy material comprises the following components by weight percentage: 15-20% of Cu, 5-10% of metal element A, 0.5-5% of compound B, and the balance is Li and inevitable impurity elements; the multinary lithium metal alloy material has the advantages of good structural stability, can inhibit the growth of lithium dendrites and the generation of dead lithium during charging and discharging, and is helpful to improve the cycle life of lithium metal batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery manufacturing, and in particular relates to a multi-component lithium metal alloy material and a preparation method thereof. Background Art

[0002] Lithium metal batteries have become an important research direction for future energy storage devices due to their high energy density and high capacity. However, it is well known that lithium metal batteries still have many problems in practical applications. On the one hand, lithium metal is prone to form lithium dendrites during repeated dissolution / electroplating processes, and these lithium dendrites may pierce the diaphragm, causing battery short circuit and failure; on the other hand, due to the relatively negative potential of lithium metal (-3.04vsRHE) and its strong reducing property, it is easy to react with conventional electrolytes to form an unstable solid electrolyte interface (SEI), which will lead to the loss of active lithium and reduced Coulomb efficiency.

[0003] The above problems seriously hinder the future application of lithium metal batteries. In order to solve the above problems, people have made great efforts, including electrolyte optimization, construction of a stable artificial SEI protective layer and modification of the diaphragm, and have made some progress. However, most of these research works are limited to less than 1mA / cm 2 Under the condition of fast charge / discharge, higher working current density will lead to more serious capacity decay and instability of the electrode, and the above measures can only have limited effect. In order to enable lithium metal batteries to meet the actual application requirements at higher current density, more effective solutions need to be further explored and developed.

[0004] In recent years, lithium alloying has been shown to play a vital role in suppressing lithium dendrite growth, controlling interfacial reactions, and improving Coulombic efficiency (CE) and cycle life. 3 N has good stability, electronic insulation and Li + transport properties, so the LiF and Li 3 On the one hand, N can promote Li + On the other hand, it can also act as a protective medium and nucleation induction medium to improve the structural stability of the lithium alloy network and the uniformity of lithium deposition during battery operation. Based on the above principles and a large number of alloy component optimization verifications, the present invention designs a multi-component lithium metal alloy material, which achieves a significant improvement in battery performance. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a multi-component lithium metal alloy material and a preparation method thereof. The multi-component lithium metal alloy material has good structural stability, can inhibit the growth of lithium dendrites and the generation of dead lithium during the charging and discharging process, and helps to improve the cycle life of lithium metal batteries.

[0006] The technical solution adopted by the present invention to solve the above technical problems is: a multi-component lithium metal alloy material, which comprises the following components by weight percentage: 15-20% Cu, 5-10% metal element A, 0.5-5% compound B, and the remainder is Li and unavoidable impurity elements.

[0007] Preferably, the metal element A is one of Mg, Al, Zn, Ag, In and Sn.

[0008] Preferably, the compound B is Si 3 N 4 、AlN、Zn 3 N 2 Mg 3 N 2 , AlF 3 、ZnF 2 MgF 2 , C 3 N 4 One of them.

[0009] And a method for preparing a multi-component lithium metal alloy material, comprising the following steps:

[0010] S1. In an Ar gas environment, a certain mass of pure lithium ingot is placed in a stainless steel crucible and heated to 300-500°C until the pure lithium ingot is completely melted to obtain lithium liquid;

[0011] S2, adding a certain mass of copper powder to the lithium liquid, heating and stirring to allow the copper powder and the lithium liquid to react completely to obtain a first mixed solution;

[0012] S3, adding a certain mass of metal element A to the first mixed solution, heating and stirring to allow the metal element A to react completely with the first mixed solution to obtain a second mixed solution;

[0013] S4, adding a certain amount of compound B to the second mixed solution, heating and stirring to allow compound B to react completely with the second mixed solution to obtain an alloy mixed solution;

[0014] S5, casting the alloy mixture into a stainless steel mold, and obtaining an original alloy ingot after cooling;

[0015] S6. The original alloy ingot is subjected to rolling and processing to obtain a multi-component lithium metal alloy material.

[0016] Preferably, the multi-component lithium metal alloy material comprises the following components by weight percentage: 15-20% Cu, 5-10% metal element A, 0.5-5% compound B, and the remainder is Li and unavoidable impurity elements.

[0017] Preferably, in step S1, the heating time is 30±5 min.

[0018] Preferably, in step S2, the heating temperature is 500±50°C, the heating time is 60±10min, and the stirring rate is 300-500r / min.

[0019] Preferably, in step S3, the metal element A is one of Mg, Al, Zn, Ag, In and Sn, the heating temperature is 500±50°C, the heating time is 60±10min, and the stirring rate is 300-400r / min.

[0020] Preferably, in step S4, compound B is Si 3 N 4 、AlN、Zn 3 N 2 Mg 3 N 2 , AlF 3 、ZnF 2 MgF 2 , C 3 N 4 The heating temperature is 500±50°C, the heating time is 60±10min, and the stirring rate is 300-400r / min.

[0021] Compared with the prior art, the advantages of the present invention are:

[0022] 1. Through the element design of the alloy, a three-dimensional fast transmission network of electrons and lithium ions is constructed, which not only has good structural stability, but also can inhibit the growth of lithium dendrites and the generation of dead lithium during the charging and discharging process, which helps to improve the cycle life of lithium metal batteries;

[0023] 2. The multi-component lithium metal alloy material has a stable three-dimensional main structure to accommodate active lithium, thereby eliminating damage to the electrode and interface caused by volume change;

[0024] 3. The multi-component lithium metal alloy material has a large electroactive specific surface area and abundant lithium deposition / dissolution active sites, which can effectively reduce the local current density;

[0025] 4. The multi-component lithium metal alloy material has electrochemical inertness and good mechanical stability;

[0026] 5. The multi-component lithium metal alloy material has a SEI film with a high Li+ transmission rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The cycle life curves of the lithium metal batteries of Examples 1-5 and the lithium metal battery of Comparative Example 1. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0029] Example

[0030] A multi-component lithium metal alloy material, which comprises the following components by weight percentage: 15-20% Cu, 5-10% metal element A, 0.5-5% compound B, and the balance is Li and unavoidable impurity elements, wherein the metal element A is one of Mg, Al, Zn, Ag, In, Sn, and the compound B is Si 3 N 4 、AlN、Zn 3 N 2 Mg 3 N 2 , AlF 3 、ZnF 2 MgF 2 , C 3 N 4 One of them.

[0031] The method for preparing the multinary lithium metal alloy material comprises the following steps:

[0032] S1. In an Ar gas environment, a certain mass of pure lithium ingot is placed in a stainless steel crucible and heated to 300-500°C until the pure lithium ingot is completely melted to obtain lithium liquid;

[0033] S2, adding a certain mass of copper powder to the lithium liquid, heating and stirring to allow the copper powder and the lithium liquid to react completely to obtain a first mixed solution;

[0034] S3, adding a certain mass of metal element A to the first mixed solution, heating and stirring to allow the metal element A to react completely with the first mixed solution to obtain a second mixed solution;

[0035] S4, adding a certain amount of compound B to the second mixed solution, heating and stirring to allow compound B to react completely with the second mixed solution to obtain an alloy mixed solution;

[0036] S5, casting the alloy mixture into a stainless steel mold, and obtaining an original alloy ingot after cooling;

[0037] S6. The original alloy ingot is subjected to rolling and processing to obtain a multi-component lithium metal alloy material.

[0038] In step S1, the heating time is 30±5 min.

[0039] In step S2, the heating temperature is 500±50°C, the heating time is 60±10min, and the stirring rate is 300-500r / min.

[0040] In step S3, the heating temperature is 500±50°C, the heating time is 60±10min, and the stirring rate is 300-400r / min.

[0041] In step S4, the heating temperature is 500±50°C, the heating time is 60±10min, and the stirring rate is 300-400r / min.

[0042] Embodiment 1,

[0043] A method for preparing a multi-component lithium metal alloy material comprises the following steps:

[0044] S1. In an Ar gas environment, 7.0 g of pure lithium ingot was placed in a stainless steel crucible and heated to 300°C for 30 min until the pure lithium ingot was completely melted to obtain lithium liquid.

[0045] S2, adding 1.5 g of copper powder to the lithium solution, heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 400 r / min to allow the copper powder and the lithium solution to react completely to obtain a first mixed solution;

[0046] S3, adding 1.0 g of pure tin particles to the first mixed solution, heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 400 r / min to allow the pure tin particles to react completely with the first mixed solution to obtain a second mixed solution;

[0047] S4, add 0.5g of silicon nitride powder (Si 3 N 4 ), heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 300 r / min to allow the silicon nitride powder and the second mixed solution to react completely to obtain an alloy mixed solution;

[0048] S5. Cast the alloy mixture into a stainless steel mold and obtain Li-15Cu-10Sn-5Si after cooling. 3 N 4 Original alloy ingot;

[0049] S6. The original alloy ingot is rolled and subjected to rolling to obtain a multi-component lithium metal alloy material with a thickness of 80 μm.

[0050] Embodiment 2,

[0051] A method for preparing a multi-component lithium metal alloy material comprises the following steps:

[0052] S1. In an Ar gas environment, 7.45 g of pure lithium ingot was placed in a stainless steel crucible and heated to 300°C for 30 min until the pure lithium ingot was completely melted to obtain lithium liquid.

[0053] S2, adding 2.0 g of copper powder to the lithium solution, heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 400 r / min to allow the copper powder and the lithium solution to react completely to obtain a first mixed solution;

[0054] S3, adding 0.5 g of pure zinc particles to the first mixed solution, heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 400 r / min to allow the pure tin particles to react completely with the first mixed solution to obtain a second mixed solution;

[0055] S4, add 0.05g of pure ZnF to the second mixed solution 2 powder, heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 300 r / min to allow the silicon nitride powder and the second mixed liquid to react completely to obtain an alloy mixed liquid;

[0056] S5. Cast the alloy mixture into a stainless steel mold and obtain Li-20Cu-5Zn-0.5ZnF after cooling. 2 Original alloy ingot;

[0057] S6. The original alloy ingot is rolled and subjected to rolling to obtain a multi-component lithium metal alloy material with a thickness of 80 μm.

[0058] Embodiment 3,

[0059] A method for preparing a multi-component lithium metal alloy material comprises the following steps:

[0060] S1. In an Ar gas environment, 7.45 g of pure lithium ingot was placed in a stainless steel crucible and heated to 300°C for 30 min until the pure lithium ingot was completely melted to obtain lithium liquid.

[0061] S2, adding 2.0 g of copper powder to the lithium solution, heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 400 r / min to allow the copper powder and the lithium solution to react completely to obtain a first mixed solution;

[0062] S3, adding 0.5 g of pure zinc particles to the first mixed solution, heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 400 r / min to allow the pure tin particles to react completely with the first mixed solution to obtain a second mixed solution;

[0063] S4, add 0.05g AlF 3 powder, heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 300 r / min to allow the silicon nitride powder and the second mixed liquid to react completely to obtain an alloy mixed liquid;

[0064] S5. Cast the alloy mixture into a stainless steel mold and obtain Li-20Cu-5Zn-0.5AlF 3 Original alloy ingot;

[0065] S6. The original alloy ingot is rolled and subjected to rolling to obtain a multi-component lithium metal alloy material with a thickness of 80 μm.

[0066] Embodiment 4,

[0067] A method for preparing a multi-component lithium metal alloy material comprises the following steps:

[0068] S1. In an Ar gas environment, 7.45 g of pure lithium ingot was placed in a stainless steel crucible and heated to 300°C for 30 min until the pure lithium ingot was completely melted to obtain lithium liquid.

[0069] S2, adding 2.0 g of copper powder to the lithium solution, heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 400 r / min to allow the copper powder and the lithium solution to react completely to obtain a first mixed solution;

[0070] S3, adding 0.5 g of pure zinc particles to the first mixed solution, heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 400 r / min to allow the pure tin particles to react completely with the first mixed solution to obtain a second mixed solution;

[0071] S4, adding 0.05 g of AlN powder to the second mixed solution, heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 300 r / min to allow the silicon nitride powder and the second mixed solution to react completely, to obtain an alloy mixed solution;

[0072] S5, casting the alloy mixture into a stainless steel mold, and obtaining a Li-20Cu-5Zn-0.5AlN original alloy ingot after cooling;

[0073] S6. The original alloy ingot is rolled and subjected to rolling to obtain a multi-component lithium metal alloy material with a thickness of 80 μm.

[0074] Embodiment 5,

[0075] A method for preparing a multi-component lithium metal alloy material comprises the following steps:

[0076] S1. In an Ar gas environment, 7.45 g of pure lithium ingot was placed in a stainless steel crucible and heated to 300°C for 30 min until the pure lithium ingot was completely melted to obtain lithium liquid.

[0077] S2, adding 2.0 g of copper powder to the lithium solution, heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 400 r / min to allow the copper powder and the lithium solution to react completely to obtain a first mixed solution;

[0078] S3, adding 0.5 g of pure zinc particles to the first mixed solution, heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 400 r / min to allow the pure tin particles to react completely with the first mixed solution to obtain a second mixed solution;

[0079] S4, add 0.05g of C to the second mixed solution 3 N 4 powder, heating and stirring at a heating temperature of 500° C., a heating time of 60 min, and a stirring rate of 300 r / min to allow the silicon nitride powder and the second mixed liquid to react completely to obtain an alloy mixed liquid;

[0080] S5. Cast the alloy mixture into a stainless steel mold and obtain Li-20Cu-5Zn-0.5C after cooling. 3 N 4 Original alloy ingot;

[0081] S6. The original alloy ingot is rolled and subjected to rolling to obtain a multi-component lithium metal alloy material with a thickness of 80 μm.

[0082] Comparative Example 1

[0083] Pure lithium sheets, battery separators, electrolytes and ternary NCM6 systems are assembled together to form lithium metal batteries.

[0084] The multi-component lithium metal alloy material prepared in Examples 1-5 was die-cut to obtain a negative electrode sheet according to the size of the battery to be assembled. The negative electrode sheet, battery separator, electrolyte and ternary NCM6 system were assembled into a lithium metal battery. The lithium metal battery composed above and the lithium metal battery of Comparative Example 1 were subjected to charge and discharge cycle tests. The battery was charged to 4.35V at a rate of 1.0C, and then discharged to 3.0V at a rate of 1.0C. The cycle was repeated, and the number of cycles when the discharge capacity was reduced to 80% was recorded. The results are shown in the following table and Figure 1 As shown:

[0085]

[0086] According to the above table, compared with conventional pure lithium negative electrode sheets, the number of cycles of lithium metal batteries composed of the multi-component lithium metal alloy material can be increased by more than 20%, up to 47%, and the cycle performance is significantly improved. It can be seen that the multi-component lithium metal alloy material can play an important role in inhibiting volume changes, inhibiting lithium dendrite growth, inhibiting interfacial side reactions, and improving Coulomb efficiency and cycle life.

[0087] The above is an exemplary description of the present invention. Obviously, the implementation of the present invention is not limited to the above-mentioned method. As long as various improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A multi-component lithium metal alloy material, characterized in that: The multi-component lithium metal alloy material comprises the following components by weight percentage: 15-20% Cu, 5-10% metal element A, 0.5-5% compound B, and the remainder is Li and unavoidable impurity elements.

2. The multinary lithium metal alloy material according to claim 1, characterized in that: The metal element A is one of Mg, Al, Zn, Ag, In and Sn.

3. The multi-component lithium metal alloy material according to claim 1, characterized in that: The compound B is one of Si3N4, AlN, Zn3N2, Mg3N2, AlF3, ZnF2, MgF2, and C3N4.

4. A method for preparing a multinary lithium metal alloy material, characterized in that: The following steps are involved: S1. In an Ar gas environment, a certain mass of pure lithium ingot is placed in a stainless steel crucible and heated to 300-500°C until the pure lithium ingot is completely melted to obtain lithium liquid; S2, adding a certain mass of copper powder to the lithium liquid, heating and stirring to allow the copper powder and the lithium liquid to react completely to obtain a first mixed solution; S3, adding a certain mass of metal element A to the first mixed solution, heating and stirring to allow the metal element A to react completely with the first mixed solution to obtain a second mixed solution; S4, adding a certain mass of compound B to the second mixed solution, heating and stirring to allow compound B to react completely with the second mixed solution to obtain an alloy mixed solution; S5, casting the alloy mixture into a stainless steel mold, and obtaining an original alloy ingot after cooling; S6. The original alloy ingot is subjected to rolling and processing to obtain a multi-component lithium metal alloy material.

5. The method for preparing a multinary lithium metal alloy material according to claim 4, characterized in that: The multi-component lithium metal alloy material comprises the following components by weight percentage: 15-20% Cu, 5-10% metal element A, 0.5-5% compound B, and the remainder is Li and unavoidable impurity elements.

6. The method for preparing a multinary lithium metal alloy material according to claim 4, characterized in that: In step S1, the heating time is 30±5 min.

7. The method for preparing a multinary lithium metal alloy material according to claim 4, characterized in that: In step S2, the heating temperature is 500±50°C, the heating time is 60±10min, and the stirring rate is 300-500r / min.

8. The method for preparing a multinary lithium metal alloy material according to claim 4, characterized in that: In step S3, the metal element A is one of Mg, Al, Zn, Ag, In, and Sn, the heating temperature is 500±50° C., the heating time is 60±10 min, and the stirring rate is 300-400 r / min.

9. The method for preparing a multinary lithium metal alloy material according to claim 4, characterized in that: In step S4, compound B is one of Si3N4, AlN, Zn3N2, Mg3N2, AlF3, ZnF2, MgF2, and C3N4, the heating temperature is 500±50°C, the heating time is 60±10min, and the stirring rate is 300-400r / min.